Project Report on A Study of Road Network A Case Study in Bangalore Metropolitan - TEJ NARAYAN YADAV , RANA PRATAP SINGH , MANOJ KUMAR SINGH and ABBAS M D (1992)
INTERNAL GUIDE: T N THYAGARAJA. CIVIL DEPT MVJCE
Keywords: A Study of Road Network A Case Study in Bangalore Metropolitan